Synthesis and physical properties of four hexazapentacene derivatives - Li, Gang (2013)
In two steps from commercially available starting materials, four novel hexazapentacene derivatives have been synthesized through cyclocondensation reaction between tetraamines and 1,2-diketones. The observed optical bandgaps for 2,3,9,10-tetramethyl-1,4,6,8,11,13-hexaza-pentacene (TMHAP, 1), tetraethyl-1,4,6,8,11,13-hexaza-pentacene (TEHAP, 2), 1,2,3,4,10,11,12,13-octahydro-5,7, 9,14,16,18-hexazaheptacene (OHHAH, 3), and tetra(2-thioyl)-1,4,6,8,11,13-hexazapentacene (TTHAP, 4) are 2.55, 2.55, 2.45, and 2.25 eV, respectively. The cyclic voltammetry measurements show that all compounds exhibit one revisable reduction waves. The calculated bandgaps through DFT calculations for TMHAP (1), TEHAP (2), OHAH (3), and TTHAP (4) are 2.41, 2.41, 2.34, and 2.15 eV, respectivly, which are close to the experimental results. Our success in synthesizing hexazapentacene derivatives might offer a promising strategy to challenge larger azaacenes with more N atoms.